2021
DOI: 10.3390/foods10040699
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Effects on Natural-Sourced Polysacchrides: Free Radical Formation/Production, Degradation Process, and Reaction Mechanism—A Critical Synopsis

Abstract: Numerous reactive oxygen species (ROS) entities exist, and hydrogen peroxide (H2O2) is very key among them as it is well known to possess a stable but poor reactivity capable of generating free radicals. Considered among reactive atoms, molecules, and compounds with electron-rich sites, free radicals emerging from metabolic reactions during cellular respirations can induce oxidative stress and cause cellular structure damage, resulting in diverse life-threatening diseases when produced in excess. Therefore, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 202 publications
(373 reference statements)
0
38
0
Order By: Relevance
“…On the other hand, the total phenolic content range of processed rubber seed meals (0.50–2.77 mg GAE/g) (Refer to Table 1 ) compares favourably with that Mujic et al (2011) reported for soybean (0.87 to 2.16 mg GAE/g). Phenols are important in enhancing the nutritional value in foods, acting as antioxidants (that can prevent cellular damage due to free radical oxidation reactions) as well as anti-inflammatory agents ( Reis-Giada, 2013 ; Ofoedu et al, 2021 ). The flavonoids content of RRSM (60.00 mg QE/100 g), BRSM (40.00 mg QE/100 g), and FRSM (52.50 mg QE/100 g) ( Table 1 ) compares favourably with those of soybean (51 mg/100 g) ( Josipovic et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the total phenolic content range of processed rubber seed meals (0.50–2.77 mg GAE/g) (Refer to Table 1 ) compares favourably with that Mujic et al (2011) reported for soybean (0.87 to 2.16 mg GAE/g). Phenols are important in enhancing the nutritional value in foods, acting as antioxidants (that can prevent cellular damage due to free radical oxidation reactions) as well as anti-inflammatory agents ( Reis-Giada, 2013 ; Ofoedu et al, 2021 ). The flavonoids content of RRSM (60.00 mg QE/100 g), BRSM (40.00 mg QE/100 g), and FRSM (52.50 mg QE/100 g) ( Table 1 ) compares favourably with those of soybean (51 mg/100 g) ( Josipovic et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The implication of oxidative stress in a variety of chronic or neurodegenerative diseases cannot be overemphasized ( Ilkhani, Hosseini & Saedisomeolia, 2016 ; Ofoedu et al, 2021 ). As a neglected potential antioxidant micronutrient, the active form (NAD/NADP) or reduced form (NADH/NADPH) of niacin have been associated with antioxidant properties via glutathione redox cycle, which tends to combat oxidative stress, specifically, lipid peroxidation and reperfusion oxidative injury ( Ilkhani, Hosseini & Saedisomeolia, 2016 ; Fricker et al, 2018 ; Gasperi et al, 2019 ).…”
Section: Discussion Of Literature Synthesismentioning
confidence: 99%
“…On the other hand, the synergistic action of vitamins and minerals in the protection of organism at the cellular level has been recorded for vitamin E, C, carotenoid and selenium, as well as other important trace elements as an antioxidant component in diets. Specifically, these indispensable antioxidant vitamins and selenium, interact to protect tissues from free-radical degradation by quenching active (singlet) oxygen species, sequestering elements by chelation, and scavenging reactive oxygen species ( DeLaval, 2007 ; McDowell et al, 2007 ; Ofoedu et al, 2021 ).…”
Section: Discussion Of Literature Synthesismentioning
confidence: 99%
“…It is widely accepted that there are two mechanisms of reducing hydroxyl radicals in polysaccharides. One is removing hydroxyl radicals by hydrogen electron transfer or single electron transfer, the other is the formation of free radicals which were inhibited by chelation transition metal ions (Ofoedu et al, 2021). WPEP and DWPEP function mainly through the primary mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Polysaccharides isolated from P. edulis peel can also effectively regulate blood glucose and lipid levels, regulate intestinal short chain fatty acids content and GLP-1R, and promote insulin secretion (da Silva et al, 2014). However, in recent years, some studies have demonstrated that the Mw of polysaccharides will limit their biological activities (Ma et al, 2018;Ofoedu et al, 2021;Zhang et al, 2014). But this seems to be improved by Vc-H 2 O 2 degradation.…”
mentioning
confidence: 99%